Placentation in the capybara (Hydrochaerus hydrochaeris), agouti (Dasyprocta aguti) and paca (Agouti paca) - Miglino, M.; Carter, A. M.; Ferraz, RHD; Machado, MRF (W B Saunders Co Ltd, 2002)
Placentae of three hystricimorph rodents-capybara, agouti and paca-were examined by conventional histology, immunohistochemistry for cytokeratin and vimentin, and TUNEL staining. The placentae were divided into lobules of labyrinthine syncytium separated by interlobular and marginal trophoblast. The subplacenta comprised cytotrophoblasts, supported on lamellae of allantoic mesoderm, and syncytiotrophoblast. The central excavation was still apparent in the definitive placenta of capybara. In agouti and paca, the decidua of the junctional zone formed a mesoplacenta comprising a capsule and a pedicle. Towards term the pedicle formed a tenuous attachment between placenta and uterine wall comprising a few maternal vessels surrounded by degraded tissue. In paca placenta, it was shown by TUNEL staining that breakdown of this tissue occurred by apoptosis. The visceral yolk sac was highly villous and, in agouti, the yolk sac villi were extremely long. Lateral to its attachment to the placenta, the fetal surface was covered with non-vascular yolk sac endoderm. A layer of spongiotrophoblast cells was interposed between the endoderm and the marginal trophoblast. (C) 2002 Elsevier B.V. Ltd. All rights reserved.